Do community needs affect the decision to volunteer? The case of refugees in Germany. - Tassi, Annalisa (Journal of Economic Behavior & Organization, 2024)

Purchasing Time: The First 100 Days of German COVID-19 Policy - Müller, Michael W.; Tassi, Annalisa; Döbbeling, Niklas; Hildebrandt, Friederike (Springer Nature, 2023)
The chapter analyzes the first 100 days of German COVID-19 policy focusing on the legal and economic responses to the immediate outbreak of the Coronavirus and the accompanying public debate. While there have been demanding measures against the spread of the virus from the beginning on, first studies suggest a high level of compliance with such measures. At the same time, significant material support was provided in the form of financial relief for businesses and individuals. With the crisis further progressing, however, it has been criticized that the relief measures were neither able to fairly distribute the burdens of the pandemic nor could they be upheld for long without endangering public finances. All this suggests that Germany, in the early days of the pandemic, was able to purchase time without, however, designing a sustainable framework for intervention and burden-sharing.
CRIS-Team Scopus Importer:2023-10-06

VAT Fraud and Reverse Charge: Empirical Evidence from VAT Return Data - Büttner, Thiess; Tassi, Annalisa (International Tax and Public Finance, 2023)